Upaya Meningkatkan Kemampuan Mengenal Angka Melalui Media Kartu Angka - Gaudensiana Delsi; Priska Benedikta Jenahat; Selvina Wallu; Ni Komang Ayu Sri Lestari (Early Childhood Education Development and Studies (ECEDS), 2021)
The purpose of this classroom action research is: to find out how to increase the ability to recognize numbers through a number card media game in group B at Kindergarten, North Rahong Utara in 2022/2023. The research subjects were group B TK Negeri Rahong Utara, North Rahong Utara, Manggarai district, in the academic year 2022/2023, which consisted of 26 TK of 12 boys and 14 girls with an average age of 5 years.This research was conducted in group B of North Rahong Utara, North Rahong Utara, Manggarai district, which is the place of assignment of researchers where this kindergarten is located in the Ruteng Watu Benta 3 Middle School environment and is adjacent to the north of residents' houses, to the south of Watu Benta Elementary School.This research was conducted using two cycles, with each cycle held 3 meetings. This research was conducted for approximately three months, from June to July. Based on the results of the study, it can be concluded that the application of number card media can increase activity and the ability to recognize numbers through number card media activities in group B children in North Rahong Utara Kindergarten. This increase can be seen from the acquisition of children's activity scores, teacher activity and class average scores and the level of classical completeness in each cycle has increased in cycle I and cycle II.